Potential vorticity tendency aspects of the motion of typhoon muifa (2004) - Pajuelas, Bonifacio G. (Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliiman, 2008)
This study attempts to determine the dominant influence on the motion of tropical cyclone (TC) Muifa (2004) using the expanded potential vorticity tendency (PVT) framework to explain TC motion. The framework suggests that a TC is likely to move towards the region of maximum asymmetric PVT which is mainly contributed by the asymmetric components of potential vorticity (PV) advection and diabatic heating (DH)